Answer:
0
Step-by-step explanation:
h(t) = (t + 3)² + 5, -5 ≤ t ≤ -1
The average rate of change is the change in h over the change in t.
(h(-1) − h(-5)) / (-1 − (-5))
= ((-1 + 3)² + 5 − ((-5 + 3)² + 5)) / (-1 + 5)
= (4 + 5 − 4 − 5)) / 4
= 0
8(x-2) = 3(x+3) I am not sure what we were supposed to do because you did not state what form we are converting this to.
Answer:
110 is the answers for the question
Step-by-step explanation:
please mark me as brainlest
X + 3y = 7
y = 2
Substitute
x + 3(2) = 7
x + 6 = 7
x = 1
Hope this helps!<span />
Answer:
Theta = 59 degrees
Step-by-step explanation:
Here, we want to get the value of the marked angle
To do this, we use the appropriate trigonometric ratio
From what we have,
The side 42 ft is adjacent the angle given
The side facing the right angle is 82 ft
The trigonometric ratio that connects the adjacent and the hypotenuse is cosine. It is the ratio of the adjacent to the hypotenuse
Cos theta = 42/82
theta = cos^-1 0.5122
theta= 59.189
To the nearest degrees, this is 59 degrees